Analisis Kesiapan Penggunaan RME dalam Pelayanan Anestesi di RS Jawa Barat - Widianto, Asriadi Prihandika; Wahyudi, Fikri Mourly; Noprianty, Richa (Bandung Conference Series: Medical Science, 2025)
Abstract. The implementation of Electronic Medical Records (EMR) is mandatory for hospitals based on Ministry of Health Regulation No. 24 of 2022 on Medical Records. However, its application in the Central Surgical Installation (CSI) of Hospital X in West Java still faces challenges. This study aims to evaluate the readiness for completing anesthesia records within the EMR system in this unit. A descriptive qualitative case study design was conducted using the HOT-Fit evaluation model (Human, Organization, Technology, and Net Benefit). Data were collected through in-depth interviews with six informants from various professional backgrounds, including nurse anesthetist, medical record staff, hospital management, and IT personnel. Data analysis was conducted using NVivo 12, and ethical approval was obtained (070/11/EthicalClearance/RSX/III/2025). Triangulation was performed by involving IT staff as the system vendor. The study identified six key findings: user transformation, organizational readiness, technological readiness, technology sustainability, clinical and operational benefits, and administrative and managerial benefits. Results indicate that readiness for electronic anesthesia record completion considered low, particularly regarding human resources, organizational support, and technology. The EMR system is not yet fully integrated, with barriers in training, infrastructure, and inter-unit coordination. Strengthening the system, enhancing training, and conducting regular evaluations are essential for more effective implementation.. Abstrak. Implementasi Rekam Medis Elektronik (RME) merupakan kewajiban rumah sakit berdasarkan Permenkes No. 24 Tahun 2022 tentang Rekam Medis, namun penerapannya di Instalasi Bedah Sentral (IBS) Rumah Sakit X di Jawa Barat masih menghadapi tantangan. Penelitian ini bertujuan mengevaluasi kesiapan pengisian kartu anestesi dalam sistem RME di unit tersebut. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kasus, mengadopsi model evaluasi HOT-Fit (Human, Organization, Technology, dan Net Benefit). Data diperoleh melalui wawancara mendalam terhadap enam informan dari berbagai latar belakang profesi (penata anestesi, staf rekam medis, manajemen, dan IT). Analisis data menggunakan aplikasi NVivo 12 dan telah memperoleh izin etik (070/11/EthicalClearance/RSX/III/2025). Triangulasi data dilakukan dengan melibatkan staf IT sebagai vendor sistem IT. Penelitian ini menemukan enam temuan utama, yaitu transformasi pengguna, kesiapan organisasi, kesiapan teknologi, keberlanjutan teknologi, manfaat klinis dan operasional, serta manfaat administratif dan manajerial. Hasil penelitian menunjukkan kesiapan pengisian kartu anestesi elektronik masih rendah, terutama dalam aspek sumber daya manusia, organisasi, dan teknologi. Sistem RME belum sepenuhnya terintegrasi dan masih menghadapi kendala dalam pelatihan, infrastruktur, serta koordinasi lintas unit. Meski demikian, terdapat potensi manfaat signifikan, secara klinis dan administratif. Oleh karena itu, diperlukan penguatan sistem, peningkatan pelatihan, dan evaluasi rutin untuk mendukung implementasi yang lebih efektif.